Pigment diversity and biomass of phytoplankton in lentic water bodies of Bhadravathi taluk, Karnataka-India - Naik T2, Ajayan K.V1; Parameswara (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present investigation revealed that biomass of phytoplankton by chlorophyll estimation method shows that Chl.a, Chl.b and Chl.c distributions were unequal. The minimum concentration of Chl.a was 0.112mg/L during November at BVTS3 and maximum .077 mg/L was recorded same station in the month of December. The Chl.b concentration was 0.0023mg/L minimum during October at BVTS1 and maximum 0.6118mg/L during August at BVTS3 and 0.0083 mg/L Chl.c was minimum during October at BVTS3 and maximum 3.894 in October at BVTS4.The correlation coefficient of six physico-chemical parameters show fluctuating the positive and negative correlation with different chlorophyll pigments.Ã‚Â The Chl.c shows positive correlation with magnesium but others not. In BVTS1 of Chl.a, b and c show positive correlation with water temperature, pH bicarbonate and other stations were not showed the positive correlation.